2008
DOI: 10.1111/j.1537-2995.2008.01760.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term serologic follow‐up of blood donors with biologic false reactivity on an anti‐human T‐cell lymphotropic virus Types I and II chemiluminescent immunoassay and implications for donor management

Abstract: The results of this study indicate that although biologic false reactivity is usually transient, the time for resolution is variable. Allowing donors to give two or three BFR results before notification and deferral is one strategy that would substantially reduce the number of donors requiring deferral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(70 reference statements)
2
5
0
Order By: Relevance
“…Both donations were from the same donor and were NR on a secondary anti‐HIV‐1/2 EIA, and HIV‐1 RNA was not detected by routine NAT screening. The two donations were taken approximately 18 months apart, which is consistent with previous reports indicating that while anti‐HIV biologic false reactivity can be transitory, it may often persist for several years 22‐24 . While our results demonstrate that high s/co ratios on the PRISM HIV O Plus ChLIA may sometimes represent biologic false reactivity, anti‐HIV confirmed‐positive individuals without detectable HIV RNA have been reported 25‐29 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Both donations were from the same donor and were NR on a secondary anti‐HIV‐1/2 EIA, and HIV‐1 RNA was not detected by routine NAT screening. The two donations were taken approximately 18 months apart, which is consistent with previous reports indicating that while anti‐HIV biologic false reactivity can be transitory, it may often persist for several years 22‐24 . While our results demonstrate that high s/co ratios on the PRISM HIV O Plus ChLIA may sometimes represent biologic false reactivity, anti‐HIV confirmed‐positive individuals without detectable HIV RNA have been reported 25‐29 .…”
Section: Discussionsupporting
confidence: 89%
“…The two donations were taken approximately 18 months apart, which is consistent with previous reports indicating that while anti-HIV biologic false reactivity can be transitory, it may often persist for several years. [22][23][24] While our results demonstrate that high s/co ratios on the PRISM HIV O Plus ChLIA may sometimes represent biologic false reactivity, anti-HIV confirmedpositive individuals without detectable HIV RNA have been reported. [25][26][27][28][29] Therefore, it is important that donor samples that test RR on an anti-HIV IA but NR by HIV NAT are subject to serologic confirmatory testing to clarify the anti-HIV status of the donor.…”
Section: Discussionmentioning
confidence: 99%
“…For those donors who gave a second FP result, between 74·5% and 84·6% continued to give FP results at subsequent donations during the study period. A subsequent longer term study of Australian donors with FP anti‐HTLV IA results indicated that while approximately 53% of FP results were transient (Table ), they can take several months to several years to resolve . This is also consistent with studies that have reported indeterminate anti‐HTLV and anti‐HCV IB results, even when they are considered to represent FP results, can persist for several years .…”
Section: False Positive Results: Unintended Consequencessupporting
confidence: 66%
“…The Australian policy for HTLV‐I/II is that BFR donors can continue to donate with their reactive plasma used for the manufacture of plasma‐derived products. In the Australian study, none of the donors subsequently gave an anti‐HTLV–indeterminate or confirmed‐positive result during the study period, among whom 89 (26.8%) gave nonreactive donations only, 59 (17.8%) gave intermittent BFR or nonreactive donations, 56 (16.9%) gave BFR donations only, 43 (13.0%) gave BFR and then nonreactive donations, and 85 (25.6%) gave no subsequent donations 16 . Of note, all of the donors in the second, third, and fourth groups had RR results twice and would have been indefinitely deferred under the testing algorithm required by the FDA.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, all of the donors in the second, third, and fourth groups had RR results twice and would have been indefinitely deferred under the testing algorithm required by the FDA. The study projected that allowing donors to give two BFR donations (either consecutively or within 12 months) would result in a 50% reduction in the number of donors who would require notification and deferral compared to notifying donors after a single BFR episode; allowing donors up to three BFR donations (either consecutively or within 12 months) resulted in a further 50% reduction in the number of donors requiring notification and deferral 16 …”
Section: Discussionmentioning
confidence: 99%